Contributing factors of safety culture in the education sector: A systematic review - Siti Noraishah, Ismail; Azizan, Ramli; Eka Prasetya, Tofan Agung; Rosanti, Eka (Semarak Ilmu Publishing, 2025)
The practices of safety culture at industrial sectors are common but it rarely discusses in education sector. The safety culture is aim to reduce the potential of accident as well as lowering the reoccurrence of accidents. Moreover, the study on the contributing factor to form a safety culture in the education sector or learning institutions is still lacking. The objective of study is to investigate the trends of safety culture studies and its contributing factors in the education sector in year 2019 to 2023.A systematic literature review (SLR) study was conducted by applying a Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) review method has identified 17 articles on safety culture from two main databases (Science Direct and Scopus). One theme with 15 subthemes have been developed by using thematic analysis. The study found the behaviour has greatest contributing factor to form a positive safety culture was behaviour dimension (87%) followed by psychological (6.5%) and situational (6.5%). The study also found the safety training, safety awareness, safety awareness, safety knowledge, safety commitment and safety communication from behaviour dimension were the top five contributing factors to create a positive safety culture in elementary school, public and private university. In conclusion, systematic review study hopefully could increase awareness among top management level in education sector, government and policymakers in creating a safe learning environment to students.